Solve for w
w=\frac{\sqrt{13}-7}{3}\approx -1.131482908
w=\frac{-\sqrt{13}-7}{3}\approx -3.535183758
Share
Copied to clipboard
3w^{2}+15w+12-w=0
Subtract w from both sides.
3w^{2}+14w+12=0
Combine 15w and -w to get 14w.
w=\frac{-14±\sqrt{14^{2}-4\times 3\times 12}}{2\times 3}
This equation is in standard form: ax^{2}+bx+c=0. Substitute 3 for a, 14 for b, and 12 for c in the quadratic formula, \frac{-b±\sqrt{b^{2}-4ac}}{2a}.
w=\frac{-14±\sqrt{196-4\times 3\times 12}}{2\times 3}
Square 14.
w=\frac{-14±\sqrt{196-12\times 12}}{2\times 3}
Multiply -4 times 3.
w=\frac{-14±\sqrt{196-144}}{2\times 3}
Multiply -12 times 12.
w=\frac{-14±\sqrt{52}}{2\times 3}
Add 196 to -144.
w=\frac{-14±2\sqrt{13}}{2\times 3}
Take the square root of 52.
w=\frac{-14±2\sqrt{13}}{6}
Multiply 2 times 3.
w=\frac{2\sqrt{13}-14}{6}
Now solve the equation w=\frac{-14±2\sqrt{13}}{6} when ± is plus. Add -14 to 2\sqrt{13}.
w=\frac{\sqrt{13}-7}{3}
Divide -14+2\sqrt{13} by 6.
w=\frac{-2\sqrt{13}-14}{6}
Now solve the equation w=\frac{-14±2\sqrt{13}}{6} when ± is minus. Subtract 2\sqrt{13} from -14.
w=\frac{-\sqrt{13}-7}{3}
Divide -14-2\sqrt{13} by 6.
w=\frac{\sqrt{13}-7}{3} w=\frac{-\sqrt{13}-7}{3}
The equation is now solved.
3w^{2}+15w+12-w=0
Subtract w from both sides.
3w^{2}+14w+12=0
Combine 15w and -w to get 14w.
3w^{2}+14w=-12
Subtract 12 from both sides. Anything subtracted from zero gives its negation.
\frac{3w^{2}+14w}{3}=-\frac{12}{3}
Divide both sides by 3.
w^{2}+\frac{14}{3}w=-\frac{12}{3}
Dividing by 3 undoes the multiplication by 3.
w^{2}+\frac{14}{3}w=-4
Divide -12 by 3.
w^{2}+\frac{14}{3}w+\left(\frac{7}{3}\right)^{2}=-4+\left(\frac{7}{3}\right)^{2}
Divide \frac{14}{3}, the coefficient of the x term, by 2 to get \frac{7}{3}. Then add the square of \frac{7}{3} to both sides of the equation. This step makes the left hand side of the equation a perfect square.
w^{2}+\frac{14}{3}w+\frac{49}{9}=-4+\frac{49}{9}
Square \frac{7}{3} by squaring both the numerator and the denominator of the fraction.
w^{2}+\frac{14}{3}w+\frac{49}{9}=\frac{13}{9}
Add -4 to \frac{49}{9}.
\left(w+\frac{7}{3}\right)^{2}=\frac{13}{9}
Factor w^{2}+\frac{14}{3}w+\frac{49}{9}. In general, when x^{2}+bx+c is a perfect square, it can always be factored as \left(x+\frac{b}{2}\right)^{2}.
\sqrt{\left(w+\frac{7}{3}\right)^{2}}=\sqrt{\frac{13}{9}}
Take the square root of both sides of the equation.
w+\frac{7}{3}=\frac{\sqrt{13}}{3} w+\frac{7}{3}=-\frac{\sqrt{13}}{3}
Simplify.
w=\frac{\sqrt{13}-7}{3} w=\frac{-\sqrt{13}-7}{3}
Subtract \frac{7}{3} from both sides of the equation.
Examples
Quadratic equation
{ x } ^ { 2 } - 4 x - 5 = 0
Trigonometry
4 \sin \theta \cos \theta = 2 \sin \theta
Linear equation
y = 3x + 4
Arithmetic
699 * 533
Matrix
\left[ \begin{array} { l l } { 2 } & { 3 } \\ { 5 } & { 4 } \end{array} \right] \left[ \begin{array} { l l l } { 2 } & { 0 } & { 3 } \\ { -1 } & { 1 } & { 5 } \end{array} \right]
Simultaneous equation
\left. \begin{cases} { 8x+2y = 46 } \\ { 7x+3y = 47 } \end{cases} \right.
Differentiation
\frac { d } { d x } \frac { ( 3 x ^ { 2 } - 2 ) } { ( x - 5 ) }
Integration
\int _ { 0 } ^ { 1 } x e ^ { - x ^ { 2 } } d x
Limits
\lim _{x \rightarrow-3} \frac{x^{2}-9}{x^{2}+2 x-3}